Assessment of Student’s Knowledge Regarding Breast Cancer at al-Muthanna University-College of Nursing - Nuha Adel Ibrahim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Although 1 in 8 women in the US may acquire breast cancer, there is optimism for 2019 with 34.8 female breast cancer rates in the governorate of Iraq. Overall, survival rates are rising. Women live longer after beating cancer. Nurse students were studied as future health care professionals. Objectives: The study's aims are to assess student knowledge of breast cancer at al-Muthanna University-College of Nursing. Methodology: The descriptive study was used for three months to analyse nursing college students' knowledge and its relationship to age, gender, and education. The study was done at Al-Muthanna University's College of Nursing. It contained 100 male and female students from three academic levels. The data was collected using a questionnaire that included 30 questions about students' understanding about breast cancer. Results: The results of the study that two-thirds of the students were female and three-quarters of the students their ages were among the youth group, most of them from the second stage, and as for their level of knowledge, it was average or acceptable in relation to the knowledge table of (30) items towards breast cancer, and therefore they obtained a degree ranging within the acceptable level Conclusion: The researcher concluded from the results of the current study that most of the nursing students at the University of Muthanna, Iraq had acceptable knowledge, but it was not sufficient to limit the spread of breast cancer, and this knowledge came to them to qualify them to educate women in the city